Noninvasive detection of twin zygosity using genome‐wide linkage disequilibrium information - Lingrong Kong; Yingjun Yang; Chao Yuan; Xing Wei; Xinyao Zhou; Jia Zhou; Ya Xing; Gang Zou; Qianqian Sun; Luyao Cai; Qiufeng Liang; Yao Zhang; et al. (Clinical and Translational Medicine)
Dear Editor, in this study, we propose a novel linkage disequilibrium information‐based noninvasive zygosity (LDNZ) assessment method in twin pregnancies. It combines fetus‐specific allele frequency analysis with LD block to reduce the number of required single nucleotide polymorphism markers and experiment costs. LDNZ method offers a noninvasive, accurate, and cost‐effective solution for zygosity assessment, addressing the need for precise obstetric care in twin pregnancies.